Applications of DSP to Explicit Dynamic FEA Simulations of Elastically-Dominated Impact Problems - Ted Diehl; Doug Carroll; Ben Nagaraj (Shock and Vibration)
Explicit Dynamic Finite Element techniques are increasingly used for simulating impact events of personal electronic devices such as portable phones and laptop computers. Unfortunately, the elastically-dominated impact behavior of these devices greatly increases the tendency of Explicit Dynamic methods to calculate noisy solutions containing high-frequency ringing, especially for acceleration and contact-force data. For numerous reasons, transient FEA results are often improperly recorded by the analyst, causing corruption by aliasing. If aliasing is avoided, other sources of distortion can still occur. For example, filtering or decimating Explicit Dynamic data typically requires extremely small normalized cutoff frequencies that can cause significant numerical problems for common DSP programs such as MATLAB. This paper presents techniques to combat the unique DSP-related challenges of Explicit Dynamic data and then demonstrates them on a very challenging transient problem of a steel ball impacting a plastic LCD display in a portable phone, correlating simulation and experimental results.